OsRACK1 Is Involved in Abscisic Acid- and H(2)O(2)-Mediated Signaling to Regulate Seed Germination in Rice (Oryza sativa, L.) - Zhang, Dongping (Public Library of Science, 2014)
The receptor for activated C kinase 1 (RACK1) is one member of the most important WD repeat–containing family of proteins found in all eukaryotes and is involved in multiple signaling pathways. However, compared with the progress in the area of mammalian RACK1, our understanding of the functions and molecular mechanisms of RACK1 in the regulation of plant growth and development is still in its infancy. In the present study, we investigated the roles of rice RACK1A gene (OsRACK1A) in controlling seed germination and its molecular mechanisms by generating a series of transgenic rice lines, of which OsRACK1A was either over-expressed or under-expressed. Our results showed that OsRACK1A positively regulated seed germination and negatively regulated the responses of seed germination to both exogenous ABA and H(2)O(2). Inhibition of ABA biosynthesis had no enhancing effect on germination, whereas inhibition of ABA catabolism significantly suppressed germination. ABA inhibition on seed germination was almost fully recovered by exogenous H(2)O(2) treatment. Quantitative analyses showed that endogenous ABA levels were significantly higher and H(2)O(2) levels significantly lower in OsRACK1A-down regulated transgenic lines as compared with those in wildtype or OsRACK1A-up regulated lines. Quantitative real-time PCR analyses showed that the transcript levels of OsRbohs and amylase genes, RAmy1A and RAmy3D, were significantly lower in OsRACK1A-down regulated transgenic lines. It is concluded that OsRACK1A positively regulates seed germination by controlling endogenous levels of ABA and H(2)O(2) and their interaction.